Membincang Kesetaraan Gender dalam Islam (Sebuah Perdebatan dalam Wacana Hermeneutik) - Laily Muthmainnah (Jurnal Filsafat "WISDOM", 2006)
Discourse on gerder equality in Islam has so far been ahermeneutical debate. This is because there are at least twomethods of interpretation: the first is interpretation as recollectionof meaning and the second is interpretation as exercise ofsuspicion. Unfortunately, these two methods have always beenbrought into conflict with each other. As a result, this situationhinders the possibility of arriving at a model of interpretation thatis elegant but still compatible with the spirit of Al Quran. In fact,what be done is to adopt the positive aspects of each method. Inthis way, it will be possible to generate a model of interpretationthat is democratic and contextual, so that religion truly becomes asystem of faith and worship which has great respect for variousgender issues.